Profile on childbirth care at a public maternity hospital - Maria Tainara dos Santos Resende; Denise Semirames Lopes; Elisiane Gomes Bonfim
Abstract Objectives: to describe the profile on childbirth care at a reference maternity hospital in the State of Piauí based on the 2018 World Health Organization Recommendations. Methods: retrospective cross-sectional quantitative study, descriptive documentary, population census, containing vaginal deliveries performed in 2017. The data was entered in Microsoft Excel for simple statistical analysis. Results: the percentages registered at the Centro Obstétrico Superior (Superior Obstetric Center) and Centro de Parto Normal (Normal Delivery Center) were, respectively, 85.5% and 98% with the presence of a companion, 34.2% and 94% used the partogram, 63.8% and 98% took non-pharmacological methods for pain relief, 74.8% and 98.7% received fluids during labor. Amniotomy at 15.2% and 17.2%, oxytocin was administered at 26.5% and 14.6% in the 1st and 2nd periods, non-lithotomic position at 39.7% and 93.4%, episiotomy 9.9% and 6.6%. After birth, 85.5% and 96% of newborns had skin-to-skin contact and, in 65.5% and 94% there were maternal breastfeeding promotion. Conclusions: this study comprehended the indicators on childbirth care service, which are, in general, better than the national and the northeast region ones. The importance of registering indicators to evaluate care is emphasized.